On Costs of Capital in Programming Approaches to Capital Budgeting - Ederington, Louis H.; Henry, William R. (Journal of Financial and Quantitative Analysis, 1979)
This paper is concerned with costs of capital in mathematical programming formulations of the problem of capital budgeting under capital rationing. It shows that there is a serious error in the method outlined by previous authors for converting the shadow prices from the solution of the dual into measures of the firm's marginal internal opportunity rates. In addition to demonstrating that the traditional approach leads to erroneous and nonsensical results, this paper presents a correct procedure for determining these rates.